2020
DOI: 10.3390/cancers12051183
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up Outcomes after Percutaneous US/CT-Guided Radiofrequency Ablation for cT1a-b Renal Masses: Experience from Single High-Volume Referral Center

Abstract: Image-guided thermal ablations are increasingly applied in the treatment of renal cancers, under the guidance of ultrasound (US) or computed tomography (CT). Sometimes, multiple ablations are needed. The aim of the present study was to evaluate the long-term results in patients with renal mass treated with radiofrequency ablation (RFA) with both US and CT, with a focus on the multiple ablations rate. 149 patients (median age 67 years) underwent RFA from January 2008 to June 2015. Median tumor diameter was 25 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 36 publications
3
16
0
Order By: Relevance
“…Image-guided thermal ablations have been introduced in the treatment of cancer as an alternative to surgery in patients not suitable for surgical treatment several years ago (21,22). Nowadays, indications have expanded, and image guided thermal ablations are applied in the treatment of a large variety of cancers (23)(24)(25)(26)(27)(28), and in some cases represent the first suggested therapeutic option instead of surgery, as for the treatment of small hepatocellular carcinoma (29). Deriving from experience in other organs, and thanks to technological advancements with the creation of small dedicated ablative devices, image-guided thermal ablations have been applied also to the treatment of thyroid disease (30)(31)(32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…Image-guided thermal ablations have been introduced in the treatment of cancer as an alternative to surgery in patients not suitable for surgical treatment several years ago (21,22). Nowadays, indications have expanded, and image guided thermal ablations are applied in the treatment of a large variety of cancers (23)(24)(25)(26)(27)(28), and in some cases represent the first suggested therapeutic option instead of surgery, as for the treatment of small hepatocellular carcinoma (29). Deriving from experience in other organs, and thanks to technological advancements with the creation of small dedicated ablative devices, image-guided thermal ablations have been applied also to the treatment of thyroid disease (30)(31)(32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that 26.5% of patients need to undergo two or more LA operations to achieve successful treatment, especially for large RCC; for tumors >4.5 cm, approximately 7.4% of patients undergo LA treatment 44 . Mauri et al 45 reported that among 149 patients treated with thermal ablations with a median follow‐up of 54 months, 18.1% received multiple successful ablations due to incomplete ablation, local tumor progression, distant tumor progression, or multiple tumor foci. Simultaneous use of ultrasound and computed tomography in ablation surgery can improve the ability to immediately detect RCC tissue that has not been sufficiently ablated, thereby guiding immediate secondary ablation.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneous use of ultrasound and computed tomography in ablation surgery can improve the ability to immediately detect RCC tissue that has not been sufficiently ablated, thereby guiding immediate secondary ablation. One of the disadvantages of image‐guided ablation is that incomplete ablation may occur, especially if the RCC is large or centrally located 45 . It should be noted that these results are mostly from large medical institutions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Image-guided thermal ablations are increasingly used in the treatment of patients with renal cancers, in particular in patients that are unfit for surgery or with previous ipsi-or contralateral renal surgeries [1][2][3]. Several different ablative modalities, including cryoablation, radiofrequency (RF), microwave (MW) and laser ablation have been successfully used in the treatment of small renal tumors, with sustained oncological results and low complications rate [4][5][6][7]. Regardless of the ablative technique applied, precise and reliable imaging is crucial in the guidance of renal thermal ablation, and for a precise early assessment of the result [8][9][10].…”
Section: Introductionmentioning
confidence: 99%